Desain Sistem Informsi Akuntansi Pesantren Berdasarkan Pedoman Akuntansi Pesantren Dalam Rangka Meningkatkan Efisiensi Dan Efektifitas Pengelolaan Pesantren - Rusmianto, Rusmianto; Rima Maulini, Rima Maulini (Jutis (Jurnal Teknik Informatika), 2023)
ABSTRACT Pesantren is a community-based institution that has a long history for the Indonesian people and has a strategic role in encouraging the progress of the Indonesian nation in various development sectors, especially building human resources and the nation's economy. A well-managed Islamic boarding school has great potential to become one of the locomotives of economic growth and the progress of the nation in the form of improving the quality of human resources and the production of goods and services. One of the characteristics of an advanced pesantren is the existence of good financial management that encourages the availability of relevant and reliable financial information for pesantren managers and other interested parties. This research will be carried out with the aim of developing an Islamic boarding school financial accounting information system and developing an accounting application for Islamic boarding school finance as well as analyzing user acceptance of the Islamic boarding school financial accounting information system. This research uses 10 Islamic boarding schools as research objects with Darul Iman Islamic Boarding School as the coordinator of research partners. The method used to develop the system is the waterfall method, while user acceptance is approached with the Technology Acceptance Model (TAM) using the simultaneous equation model (SEM) as an analytical tool. The stages of research that have been carried out are the stages of analysis and design and writing of program code and application development. The analysis phase includes identification of existing conditions, weaknesses of the current system, and identification of business process needs. While the design phase includes context design (DFD levels 0 and 1. writing the code for this program using the PHP programming language and several XAMPP supporting tools. The final results of the black box testing of the village financial management application result that the application has been running normally.